(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
The present study was conducted to know the fish drying activities, species used in fish drying and marketing channel of dried fish in Kuakata coast of Patuakhali district of Bangladesh. Sea fishes are mostly used for drying and dry fish producers collected raw fishes from arat (landing centers) (70%), fishermen (25%) and little amount from own capture (5%). It was found that 21 fish species were used for drying among them 3 species (Harpadon nehereus, Setipinna phasa, Lepturacanthus savala) were commonly used and other 18 species were fairly used. The peak fish drying season was observed at mid-October to mid-February (in Bengali Kartik to Magh). It was observed that the dry fish producers used salt to produce good quality dry fish and salt mixing rate is 2 kg salt for 30-35 kg raw fish. The duration of drying at normal weather condition is varied between 3-5 days depending on the size of fishes. After drying, the dried fishes were packed in either jute bags or polythene bags and stored at room temperature for marketing. About 95% dried fish products are sold in the wholesale market at Chittagong, Syedpur, and Dhaka and rest 5% sold to the local retail market. However, three (3) step dried fish marketing channels were observed in the study area. The producers sold their product at very lower price and it ranged between Tk. 120-3200 per Kg. The retail price of the dried fishes ranged from Tk. 200-3500 per Kg. The dry fish producers and intermediaries faced various problems like inadequate capital, natural calamities, lack of scientific knowledge and technology, price instability, lack of transport facilities, inadequate storage facilities, lack of physical marketing facilities and marketing information. Asian Australas. J. Biosci. Biotechnol. 2020, 5 (2), 48-59